Design modification and performance testing of solar assistive electric vehicle - Neupane, Sudan (Journal of Innovations in Engineering Education, 2021)
One of the front runners in the area of renewable energy today is solar power. It is a cheap and ecofriendly means of power generation. Solar power is converted into electrical energy using photovoltaic cells. This harnessed electrical energy can be used to charge battery of EV. The objective of this project is to convert IC trike into electric vehicle and then assisted by using solar energy so that the range of the vehicle can be increased. This project involved the performance testing of an electric vehicle along with comparison with solar assisted. The vehicle we used is a single seated IC trike with skeleton structure generally used for racing purposes. The aim was to implement our idea on an IC trike and afterwards with help of result obtained to extend our future work on building a real time solar assisted electric vehicle. During the testing it is found that the electric trike operate at maximum speed of 38.4 km/hr. with 17.29 km range and 21.28 km while solar assisted with speed of 34.5km/hr. The solar assisted EV in turn resulted an increment of mileage by 23% and the additional money invested will be returned in 7.8 years. Conclusively, the solar assisted EV gained range while having a decrement in speed of the vehicle. The overall experiment favored the solar assisted EV.